CORPOREIDADE ADOECIDA: OS EFEITOS PSICOSSOMÁTICOS NA REALIDADE DAS PROFESSORAS DA EDUCAÇÃO BÁSICA DO MUNICÍPIO DE SÃO PAULO – 2012 A 2017 - FONSECA, VALÉRIA LEME (2019)
The fundamental theme of this dissertation focuses on an issue that is of concern and is always focused on public debates, media and academic studies: the relationship between work and health, or rather, work and illness. In fact, even though it possesses specific characteristics, the teaching profession is not unaware of this reality, above all, because we can see, to a large extent, that this relationship has reached a significant contingent of education professionals, including in the city of São Paulo. Well for this reason, in order to narrow our focus, we chose to contemplate the situation of the teachers of the municipal public network of São Paulo, a group of the most fragile in the face of labor evils, as the bibliographical and statistical surveys lead us to believe, since according to studies (SINESP), between 2012 and 2017, a significant number of teachers of the public network of Municipality of São Paulo have the work routine handicapped by medical leave, due to illnesses such as stress, gastritis, allergies and depression, potentially emotional pathologies of origin that reveal the dimensions of illness as a reflection of the institutional and human crisis of public education. O this end, we seek to establish a correlation between the adverse conditions reported and the occurrence of emotional diseases as psychosomatic responses to the aforementioned frustrations and anguishes, which are confirmed as bodily imbalance, culminating with a pathological condition that may even impede professional continuity and even the precocity of the finitude of life. Contemplating the identified bodily and emotional manifestations with the precariousness of the teaching condition submitted to dehumanization by the bias of the gender and the category of female workers, we obtained the necessary support for our conclusions from the content analysis of theses and dissertations that dealt with this theme, in the last five years (2012 to 2017), the appropriate bibliographic analysis and the statistical analysis from the publications promoted by the category union. The theoretical references, consistent with the possible analyzes of this thematic, refer to Marx (2002; 2004), Keleman (1992), Sontag (2004), Butler (2004; 2010; 2017), Damásio (2013; 2015; 2017), Corbin, Courtine and Vigarello (2012), among other authors of equal relevance.